EFFECT OF GUAJAVA (PSIDIUM) LEAVES DECOCTION ON CHANGES IN BLOOD GLUCOSE LEVELS OF PEOPLE WITH DIABETES MELLITUS (Proceedings OPTIMAL, 2024)
Diabetes mellitus is a type of metabolic disease characterized by hyperglycemia. If this condition is not treated correctly, it can cause various complications that can lead to death. Diabetic mellitus patients are given pharmacological treatment and can be given nonpharmacological treatment with the use of plants as an alternative to lower blood sugar levels, including the use of guava leaves (psidium guajava leaf). The chemical content found in guava leaves, skin, and fruits is tannins, calcium, and flavonoids, which have the benefit of lowering blood glucose levels. This research aims to determine the effect of giving guava leaf decoction water on changes in blood glucose levels in people with diabetes mellitus. This quantitative research used a quasi-experimental design method and a non-equivalent pretest-posttest control group design. The number of respondents was 70 people divided into 2 groups, namely the intervention group of 35 people and the control group of 35. The sampling technique used was nonprobability sampling, done by consecutive sampling. The intervention group was given guava leaf boiled water for 14 days, once a day in the afternoon, with a dose of 250 ml, while the control group was only educated about diabetes mellitus. The study's results using the unpaired T-test obtained a p-value = 0.000. It is concluded that there is a change in blood glucose levels after the intervention of giving guava leaves decoction. People with diabetes mellitus suggest consuming guava leaves decoction to help control their blood glucose levels.